A chebyshev collocation spectral method for numerical simulation of incompressible flow problems - Martinez,Johnny de Jesús (2007)
This paper concerns the numerical simulation of internal recirculating flows encompassing a two-dimensional viscous incompressible flow generated inside a regularized square driven cavity and over a backward-facing step. For this purpose, the simulation is performed by using the projection method combined with a Chebyshev collocation spectral method. The incompressible Navier-Stokes equations are formulated in terms of the primitive variables, velocity and pressure. The time integration of the spectrally discretized, incompressible Navier-Stokes equations is performed by a second-order mixed explicit/implicit time integration scheme. This scheme is a combination of the Crank-Nicolson scheme operating on the diffusive terms and a second-order Adams-Bashforth scheme acting on the advective terms. The projection method is used to split the solution of the incompressible Navier-Stokes equations in two decoupled problems: the Burgers equation to predict an intermediate velocity field and the Poisson equation for the pressure, which is used to correct the intermediate velocity field and satisfy the continuity equation. Numerical simulations for flows inside a two-dimensional regularized square driven cavity for Reynolds numbers up to 10000 and over a backward-facing step for Reynolds numbers up to 875 are presented and compared with numerical results previously published, where good agreement is demonstrated.